Distribution of Patriarchal Ideology In the Khilma Anis’s Novel Hati Suhita: A Semiotic Study of Weeb Keane's Ideology - Taswirul Afkar; Wawan Hermawan; Wiwik Mardiana (UIN Salatiga, 2026)
This study examines Khilma Anis's novel Hati Suhita through the lens of semiotic ideology as outlined by Webb Keane. Semiotic ideology involves people's core assumptions about signs, their functions, and potential impacts. The research aims to uncover how signs within the novel depict patriarchal systems in pesantren families and highlight women's acts of resistance. Employing a qualitative methodology with a Peircean semiotic framework, informed by semiotic ideology, the findings indicate that: (1) the tradition of arranged marriages acts as a signifier representing patriarchal dominance in pesantren households; (2) the husband's silence and refusals symbolize naturalized masculine authority; (3) the determination and escape of the female character to her mother symbolize resistance to patriarchal dominance; and (4) a tension exists between semiotic ideologies of pesantren traditions and individual female agency. This research offers insights into how pesantren literature both reproduces and questions social power structures through signs.